Do children with mathematics learning disability in Hong Kong perceive word problems differently?. (August 2020) - Yip, Eason Sai-Kit; Wong, Terry Tin-Yau; Cheung, Sing-Hang; Chan, Kelvin King-Wun
Abstract: The current study aimed at identifying the difficulties experienced by children with mathematics learning disability (MLD) in the problem representation phase of arithmetic word problem solving using a novel problem types identification task. An MLD group ( n  = 66) and a typically achieving control group ( n  = 139) were recruited for an assessment on problem type identification as well as some domain-general and mathematics-related cognitive abilities. Results from ANCOVA showed that the MLD group scored significantly lower than the typically achieving control group on this assessment, after controlling for the effect of cognitive correlates, reading achievement and arithmetic performance. Furthermore, this assessment significantly predicted MLD membership even after taking children's arithmetic competency into account. The current study confirmed the difficulties in problem representation of arithmetic word problems experienced by students with MLD and provided evidence for the need to introduce schema instructions in mathematics classes. Highlights: A new task was developed to assess students' ability to recognise word problem types. Students with math learning disability (MLD) scored significantly lower in this task. The task significantly discriminate students with MLD from their peers.